Developing core elements and checklist items for global hospital antimicrobial stewardship programmes: a consensus approach. (January 2019) - Pulcini, C.; Binda, F.; Lamkang, A.S.; Trett, A.; Charani, E.; Goff, D.A.; Harbarth, S.; Hinrichsen, S.L.; Levy-Hara, G.; Mendelson, M.; Nathwani, D.; Gunturu, R.; et al.
Abstract: Objectives: With increasing global interest in hospital antimicrobial stewardship (AMS) programmes, there is a strong demand for core elements of AMS to be clearly defined on the basis of principles of effectiveness and affordability. To date, efforts to identify such core elements have been limited to Europe, Australia, and North America. The aim of this study was to develop a set of core elements and their related checklist items for AMS programmes that should be present in all hospitals worldwide, regardless of resource availability. Methods: A literature review was performed by searching Medline and relevant websites to retrieve a list of core elements and items that could have global relevance. These core elements and items were evaluated by an international group of AMS experts using a structured modified Delphi consensus procedure, using two-phased online in-depth questionnaires. Results: The literature review identified seven core elements and their related 29 checklist items from 48 references. Fifteen experts from 13 countries in six continents participated in the consensus procedure. Ultimately, all seven core elements were retained, as well as 28 of the initial checklist items plus one that was newly suggested, all with ≥80% agreement; 20 elements and items were rephrased. Conclusions: This consensus on core elements for hospital AMS programmes is relevant to both high- and low-to-middle-income countries and could facilitate the development of national AMS stewardship guidelines and adoption by healthcare settings worldwide.